Bearing Capacity of Floating Foundations Used PVC (Poly Vinyl Chloride) on Soft Soil With The Scale Model in the Field - Srihandayani, Susy; Putri, Desi; Kurniasih, Nuning; Dwi Putri, Lusi (International Journal of Engineering and Technology, 2018)
A soft clay soil has a low support energy, so it needs to be planned a foundation form that able to improve soil bearing capacity and estimate a maximum load that can be supported by that soil. Planning a float foundation is one of the solutions to overcome that problem. The behavior of burden degradation at float foundation which obtained from encumbering of axial introduced here. Proposed analysis based on classical theory and examination of foundation at the field. Float foundation models with different amount and dimension. At the field, a pipe which one of its ends closed tightly came into soft clay soil and then encumbered step by step. Giving an axial burden and degradation model area and noted. Boundary capacities in each foundation model estimated from the curve of load-displacement yielded of the test. From the result of theoretical analysis at a single float foundation got a proportionate result with the field result but after giving additional pile/pipe with larger one's cap got the theoretical result of bearing capacity bigger than the field result. The efficiency value of the comparison of bearing capacities theoretically that using five classic methods got more than 100%, and after giving additional pipe, the efficiency value near to 100%.Â Â